Evaluasi Kinerja Pengelolaan Air Limbah Domestik terhadap Tingkat Kekeruhan dan Kadar Escherichiacolidalam Air Tanah di Perumnas Gunung Kota Cirebon - Anisa Nur Fitri Setiarini; Mursid Rahardjo; Onny Setiani (Jurnal Kesehatan Masyarakat (Undip), 2016)
The dominant resources of water contamination in Cirebon are come from domestic activities which potentially caused an impact of groundwater. Rinjani WWTP (Wastewater Treatment Plan) is the one which serving the wastewater treatment in Perumnas Gunung, Cirebon. The purpose of this research are to determine the performance of domestic wastewater management towards the level of turbidity and Escherichia coli on ground water at Perumnas Gunung, Cirebon. Type of the research is observational using qualitative and quantitative analysis with cross sectional research methods. A qualitative samples are the employees of Wastewater division while the quantitative samples are 30 of wells water at Perumnas Gunung. The research results show that there are some lacks on the aspects of wastewater management, i.e., technically operational, institutional, financing, regulation, and public participation. WWTP effectiveness in reducing NH3 parameter rated as very effective while BOD, COD, NO3-, and TSS parameter considered less effective. Correlation test shows that there is no relationship between the range of sewerage with the well towards the turbidity level of groundwater (p value=0,147), otherwise there is a relationship between the range of sewerage with the well towards the amount of E.coli on groundwater (p value=0,002). Regression test shows that there is no effect between the range of sewerage with the well towards the amount of E.coli on groundwater (p value = 0,080). The conclusion of this research is that turbiditty level on the researched sample, about 100% samples still meet the quality standards. However, it was found the existence of groundwater contamination by E. coli on 40% sample. It is important to be aware as a result of waste water seepage from sewerage which contaminate the surrounding ground water